Judd Ofelt Analysis and Optical Properties of Rare Earth Doped Tellurite Glasses - Hong, Tran Thi; Dung, Phan Tien; Quang, Vu Xuan (Communications in Physics, 2014)
In this work, the structural characteristic and photoluminescence properties were investigated in Eu\(^{3 + }\) ions-doped B\(_{2}\)O\(_{3}\)-TeO\(_{2}\) --ZnO-Na\(_{2}\)O glasses. These glasses were prepared by the melting method in air, after that thermal annealed 350\rc{}C, 450\rc{}C and 550\rc{}C for different times. The analysis results of structure on these glasses showed the formation of micro-crystals in host glass after thermal annealed process. The photoluminescence spectra of Eu\(^{3 + }\) ions in these samples were observed. The local vibration mode around Eu\(^{3 + }\) ions was investigated by the phonon side band associated with \(^{7}\)F\(_{0}\)- \(^{5}\)D\(_{2}\) transition of Eu\(^{3 + }\). Judd-Ofelt parameters have been evaluated from photoluminescence spectra and were to predict the luminescence intensity ratios of \(^{5}\)D\(_{0} → ^{7}\)F\(_{J}\) (J=2, 4 and 6) to \(^{5}\)D\(_{0} → ^{7}\)F\(_{1}\) transition. The obtained results have been used for calculating \(Ω_{2}\), \(Ω _{4}\), \(Ω _{6}\) parameters by using Judd-Ofelt theory. These \(Ω _{2}\), \(Ω _{4}\), \(Ω _{6}\) parameters allow to derive radiative properties of Eu\(^{3 + }\) ions in glass material such as transition probabilities, radiative lifetimes and peak stimulated emission cross-section for the \(^{5}\)D\(_{0} → ^{7}\)F\(_{J}\) transitions.